Correlation of histomorphologic, histochemical and immunophenotypic findings in pituitary adenomas showing prolactin activity - (:unkn) unknown (Turkish Neurosurgical Society, 2002)
Objective: In order to study clinical, histomorphological, histochemical mid inimunohistochemical characteristics in hvperproloactinemic patients, wc undertook a comparative study of 30 pituitary adenomas, Methods: We used a group of nuclear, cytoplasmic and staining parameters for* the evaluation or morphologic features of the tumor types. Tumors showed a large spectrum from the point of histomorphological features. By using Comori reticulin stain, we distinguished hyperplasia from neoplasia. Additionally, Periodic Acid Schiff staining was used for the detection of glycoprotein Content in tumor cell cytoplasm. Twenty-six cases have been analysed using anti-prolactin monoclonal antibody, and an overall of 23 cases for anti- growth hormone monoclonal antibody immunohistochemically. Results; We fuund diffuse positivity in 15 cases, sparse positivity in 3 cases for anti-prolactin a ntibody. Three cases showed no imnuinoreactivity for prolactin. Six cases showed diffuse positivity and 2 cases showed sparse positivity for anti-growth hormone monoclonal antibody. Fifteen cases were immurtonegatjve for anti-growth hormone monoclonal antibody. Five cases were immunonegativeforPRL hut positive forGH. Four of those cases had increased serum CH levels and were presented with acromegaly. Conclusion; We concluded that there is no direct correlation between serum hormone levels and immunophenotypic expressivity of pituitary adenomas. The reason of prolactinemia in cases showing GH lmmumipositivity was thought to be a stalk effect. Using electron microscopy has to be taken into consideration to identify the type of the pituitary adenoma while having insufficient results for immunohistochemical studies.
Keywords: Hyperprolactinemia; Immunuhistochemistry; Pituitary adenoma